Total knee replacement: a randomized study of clonidine and dexmedetomidine used for epidural postoperative analgesia - Nayak, Satya Prasanna; Dhar, Rabinarayan; Mohanty, Debaprasad (International Journal of Research in Orthopaedics, 2016)
Background: Epidural anaesthesia with adjuvant is the preferred method for intra and postoperative pain relief after total knee replacement surgeries but search for ideal adjuvant for prolonging the duration of postoperative analgesia without any side effect goes on. This study was conducted to evaluate the onset, extent and duration of sensory and motor block and side effects of clonidine or dexmedetomidine when used as an adjuvant in epidural anaesthesia in total knee replacement. Methods: 60 patients of ASA status I and II, posted for total knee replacement were randomly allocated into two groups of 30 each. Group I group patients received 18 ml of 0.5% levobupivacaine and clonidine 2 mcg/kg in epidural route and Group II group patients received 18 ml of 0.5% levobupivacaine and dexmedetomidine 1.5 mcg/kg in epidural route. Intraoperative and postoperative block characteristics as well as hemodynamic parameters were observed and recorded. Results: Dexmedetomidine had an earlier onset and longer duration of sensory and motor block in comparison to clonidine. Sedation scores were statistically significant with dexmedetomidine group in comparison to clonidine group. Conclusions: Dexmedetomidine was a better than clonidine as an adjuvant to levobupivacaine in epidural anaesthesia in total knee replacement.